Analisis Pengaruh Supervisi Kepala Sekolah, Iklim Kerja , dan Kemampuan Pedagogik terhadap Kinerja Guru Paud Non Formal di Kecamatan Sagulung Kota Batam - Nadya Asmarani (JURNAL AS-SAID, 2021)
The purpose of this study is to analyze and examine whether there is influence between the principal supervision, work climate, and the ability of early childhood teachers' pedagogical on the performance of the Non-Formal in District Sagulung 2014. The study population was all early childhood educators Non Formal in Sub Sagulung. Data were analyzed using path analysis, the dependent variable (dependent) is the performance of teachers and independent variables (independent) is supervising principal, work climate, and the ability pedagoik. The results showed that the supervision of the principal does not significantly affect the performance of early childhood teachers with immediate effect by 3.0%. Work climate significantly affect the performance of teachers with immediate effect of 65.9%. Pedagogic ability not significantly affect the performance of teachers with immediate effect by 1.0%. However supervision of the principal, work climate, and the ability pedagogical jointly significantly affect the performance of teachers with immediate effect by 71.4% and the rest is influenced by other variables not examined in this study (28.4%).